Synchronic Comparative Case Studies of Variations and Conditions of a Mind Concept in Contemporary Multi-Lingual and Ethnic Societies of Africa. A Topographic Example for an Accumulation Process of Diversity of Means and Meanings Used for Communication (Type: Working Paper) - (:unkn) unknown (My University, 2008)
Regarding the perspective of diachrone linguistics we compare meanings for the concept communication a) in local languages of Africa and b) compared with the English language for equivalent terms. Based upon a set of different meanings we will argue for a variety of meanings for a term in an African language with a certain degree of specification compared to equivalent terms in another African language and another set of meanings. The observed changes in the local languages illustrate the diversity of meanings in Africa. For the integration of new words in the thesaurus with new meanings English is a typical example of a language, which produces new meanings for the concept communication replacing the local languages. (Type: Working Paper)
Keywords: African Research